A New Approach for PAPR Reduction of OFDM Signal Based on Signal Scrambling - Mohamed ABBAS; Safa GASSER; Ashraf AZİZ and Mohamed KHEDR (International Journal of Applied Methods in Electronics and Computers, 2014)
Orthogonal Frequency Division Multiplexing (OFDM) is an attractive and promising technique for fourth generation wireless communication. In general, the High Peak-to-Average Power Ratio (PAPR) of transmitted signals for OFDM systems reduces the system efficiency and hence increases the cost of the Radio Frequency (RF) power amplifier. In this paper, we propose a distortion-less PAPR reduction schemes for multi-carrier system. The new schemes combine both the Partial Transmit Sequence (PTS) and the Selected Mapping (SLM) techniques. The performance of the new schemes is measured using the Complementary Cumulative Distribution Function (CCDF) of the PAPR. The simulation results show that the two new combined schemes have a better PAPR performances compared to PTS and SLM. On the other hand, the price paid is a slight increase in the system complexity, as well as the side information transmitted.